Surface characteristics limit the vertical mobility of an invasive reptile - Thomas W. Simpson; Marleen Baling; Anne C. Gaskett; Richard C. Gibson; Steven Matthews; Jacqueline R. Beggs (Biological Invasions, 2026)
Preventing the spread of small, cryptic invasive reptiles poses an ongoing challenge for conservation and biosecurity worldwide. Physical exclusion barriers offer a potentially low-cost, non-toxic tool for limiting dispersal, but their effectiveness depends on, among other factors, a detailed understanding of how surface properties influence animal movement. We tested four commonly available fencing materials—polypropylene fabric, woven polypropylene, polythene sheet, and acrylic sheet—as potential barriers to climbing by a small Australian skink, Lampropholis delicata (Scincidae). Experiments with 18 adult skinks were conducted in enclosures under both wet and dry conditions. We quantified surface roughness using four metrics: arithmetic average roughness (Ra), total height of profile (Rt), mean spacing of profile irregularities (Rsm) and Skewness (Rsk). Climbing frequency was highest on the roughest material, polypropylene fabric (Ra = 25, Rt = 167, Rsm = 457.5 µm), with up to 60% of individuals climbing. In contrast, the smoother surfaces, polythene and acrylic, limited climbing to just 5% of trials, with climbs occurring only under wet conditions. This suggests that surface water may enhance adhesion and reduce the effectiveness of smooth barriers. Our findings indicate that simple vertical drift fences are unlikely to effectively manage the spread of L. delicata , particularly in wet environments and underscore the importance of incorporating surface roughness thresholds and moisture conditions into barrier design. Polythene sheet, shows promise for indoor containment but would require modifications such as anti-climb lips for outdoor use. Tailored exclusion strategies that integrate material science with animal behaviour and ecological context could offer scalable, environmentally friendly tools for containing and managing invasive species.